Comparación de la prevalencia, severidad de caries y su relación con estilo de vida en instituciones educativas de la comuna 12 de Ibagué 2019 (2020)
Children with a great deficit in the knowledge and care of oral hygiene come to the dental consultation, from this arises the need to correct bad habits, which trigger diseases that deteriorate the oral health of the infant, the main being dental caries, which is a multifactorial disease that affects a large population in the world, is related to multiple factors that lead to the appearance of lesions affecting the stomatognathic system.